Production of Bio Fortified Vermicompost and its Efficacy Against Onion Basal Rot Disease Caused by Fusarium oxysporum f. sp. cepae - Pakeerathan, K.; Jeyavithuyan, K.; Nirosha, A.; Mikunthan, G. (University of Agriculture, Peshawar, Pakistan, 2023)
The success of organic agriculture is relied on biologically fortified super compost to sustain the yield potential of high-yielding improved varieties as well as boost the soils that substantially store water, and nutrients, and suppress soil-borne diseases. Considering the scenario, an investigation was planned to recycle plant waste into biologically fortified vermicompost. Four substrates paddy straw, garden waste (banana and maize leaves), sawdust, and kitchen waste were used as mushroom substrate and then mushroom grown waste was converted into bio-fortified vermicompost using exotic earthworm Eisenia foetida+ Trichoderma viride + Pseudomonas fluorescens. Onion growth parameters, yield, and DSI were recorded from the experiment conducted in a complete randomized design and subjected to ANOVA using SAS 9.1. Turkey’s HSD multiple comparison test and Person-correlation analysis were performed to identify the best treatment combination at P < 0.05. The results were significant among them at P < 0.05. Bio-fortified vermicompost’s pH range was 7.28-8.11, C/N ratio was 25.01-9.96, and OMC was 22.66-51.53. Nitrogen, P and K ranges were 1.06% to 2.1%, 0.73%-1.87%, 0.654% to 1.38%. Trichoderma viride + P. fluorescens enriched showed lower DSI. The highest growth, yield parameters, and lower Fusarium basal rot incidents were recorded in T. viride and P. fluorescens fortified paddy straw and kitchen waste-based vermicompost. Actual yield of the “Poovallarai” onion is higher than the theoretical yield of 15-20 Mt/ha in paddy straw and kitchen waste-based vermicompost too. C/N ratio and growth parameters were strongly co-related (R 2  >0.5). These findings could be new eco-friendly low-cost approaches to manage soil-borne diseases as well as properly manage organic wastes into super compost.
Keywords: Organic waste; Spent mushroom substrate; Bio-fortification; Fusarium basalrot; Trichoderma viride; Pseudomonas fluorescens